2016
DOI: 10.1038/nplants.2016.49
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis AGO3 predominantly recruits 24-nt small RNAs to regulate epigenetic silencing

Abstract: Argonaute (AGO) proteins recruit 21-24-nucleotide (nt) small RNAs (sRNAs) to constitute RNA-induced silencing complexes (RISCs) to regulate gene expression at transcriptional or posttranscriptional levels(1-3). Arabidopsis encodes nine functional AGO proteins. These proteins are classified into three clusters, AGO1/5/10, AGO2/3/7 and AGO4/6/9, based on their sequence similarity, functional redundancy, as well as species and features of AGO-bound sRNAs(4-7). Although most Arabidopsis AGO proteins have been stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 31 publications
1
56
0
Order By: Relevance
“…At the same time, however, several genes in this region of chromosome I display polymorphisms including AGO3 . Phylogenetically, AGO3 is the closest homolog to AGO2 , yet except against BaMV, AGO3 has not been found to be involved in virus resistance (Jaubert et al , ; Brosseau & Moffett, ; Garcia‐Ruiz et al , ; Brosseau et al , ; Alazem et al , ), but rather appears to play a role in DNA methylation (Zhang et al , ). Moreover, although AGO3 exhibits some polymorphisms, in silico analysis revealed no correlation between any of these polymorphisms and PVX susceptibility (Table S5b).…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, however, several genes in this region of chromosome I display polymorphisms including AGO3 . Phylogenetically, AGO3 is the closest homolog to AGO2 , yet except against BaMV, AGO3 has not been found to be involved in virus resistance (Jaubert et al , ; Brosseau & Moffett, ; Garcia‐Ruiz et al , ; Brosseau et al , ; Alazem et al , ), but rather appears to play a role in DNA methylation (Zhang et al , ). Moreover, although AGO3 exhibits some polymorphisms, in silico analysis revealed no correlation between any of these polymorphisms and PVX susceptibility (Table S5b).…”
Section: Resultsmentioning
confidence: 99%
“…Our data showed that OsAGO18 and OsAGO2b transcripts increase substantially at stage 7, coincident with 24-nt phasiRNA accumulation. Moreover, a recent study on Arabidopsis AGO3 showed that this poorly characterized Argonaute mediates RdDM by binding 24-nt siRNAs (Zhang et al , 2016). Phylogenetic analysis showed that Arabidopsis AGO3 and rice OsAGO2b are close to each other (Zhang et al , 2015), suggesting that OsAGO2b could also recruit 24-nt small RNAs, such as the reproductive phasiRNAs, to regulate epigenetic modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Six micro-grams (μg) of total RNA were spiked with 5′ 32 P-labeled radioisotope-labeled 19–24 nt RNA oligos and then resolved in 15% urea-PAGE. sRNA library was constructed as previously described (Zhang et al, 2016). Briefly, sRNAs of 19–24 nt were gel-purified and ligated to a pair of adapters at the 5′ and 3′ ends by using T4 RNA ligase.…”
Section: Methodsmentioning
confidence: 99%
“…sRNA blot assays were performed with aliquots of total RNAs used for sRNA-seq according to Zhang et al (2016). Each lane contained 6 μg of total RNA.…”
Section: Methodsmentioning
confidence: 99%